Development of Curcuma xanthorrhiza Nanoemulsion as an Antibiofilm Agent against Multidrug-Resistant Candida albicans: Formulation Approach and In Vitro Evaluation - Arifah, Dzulfira; Izzah, Nurul; Pujiani, Dyah Virga; Ardilia, Abidah; Masfufatun, Masfufatun (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Candida albicans infection is a serious health concern, particularly in immunocompromised individuals, due to its ability to form biofilms that are resistant to conventional antifungal therapies. Curcuma xanthorrhiza Roxb. (temulawak) possesses antifungal properties; however, its effectiveness is limited by poor solubility and bioavailability. Nanoemulsion formulation offers a promising strategy to enhance the penetration of active compounds. This study aimed to develop and evaluate the effectiveness of temulawak nanoemulsion as an antibiofilm agent against multidrug-resistant (MDR) C. albicans. Using a post-test control group only design, the antibiofilm assay was conducted via the microtiter plate method and analyzed based on Optical Density (OD) measurements. The results showed that temulawak nanoemulsion significantly reduced biofilm formation, with an 89% reduction in OD at the 100% concentration. These findings support the potential use of temulawak nanoemulsion as an alternative therapeutic strategy for Candida albicans infections, particularly those involving drug-resistant biofilms.